2020
DOI: 10.1039/c9sm02016k
|View full text |Cite
|
Sign up to set email alerts
|

A stimuli-responsive gel impregnated surface with switchable lipophilic/oleophobic properties

Abstract: A stimuli-responsive gel impregnated surface with switchable lipophilic/oleophobic properties driven by the swelling effect of a hydrogel with controllable morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…One of the essential criteria for a coating technology to be used in aerospace engineering, is the surface icephobicity [36][37][38][39][40]. Alongside with the recent anti-icing perspectives by using heated surface [41], textured surfaces [42][43][44][45], latest approach of liquid infused surface present a low cost and programmable strategy to distinguish itself from above [46][47][48]. Here, we develop a hybrid strategy by applying a silanization layer to seal the anodized porous surface (Fig.…”
Section: Silane Assisted Superhydrophobicity and Validation Of Characteristicsmentioning
confidence: 99%
“…One of the essential criteria for a coating technology to be used in aerospace engineering, is the surface icephobicity [36][37][38][39][40]. Alongside with the recent anti-icing perspectives by using heated surface [41], textured surfaces [42][43][44][45], latest approach of liquid infused surface present a low cost and programmable strategy to distinguish itself from above [46][47][48]. Here, we develop a hybrid strategy by applying a silanization layer to seal the anodized porous surface (Fig.…”
Section: Silane Assisted Superhydrophobicity and Validation Of Characteristicsmentioning
confidence: 99%
“…Most of the external stimulus changes the chemical composition of the substrate; however, changing the surface structures also produces a change in the surface wettability. Various research groups have demonstrated the mechanical stress-responsive tunable wettability using elastic or gel materials [68][69][70][71][72][73][74][75]. Poly(tetrafluoroethylene) PTFE is the most common 21st Century Surface Science -a Handbook hydrophobic material, and Teflon tape, made with PTFE crystals, has been widely used to tune the wetting behavior by applying mechanical strain.…”
Section: Mechanically Tunable Surfacesmentioning
confidence: 99%
“…As a kind of emerging nanomaterials, CNTs are also widely used in many fields [60][61][62][63][64] . Selecting suitable materials to prepare various sensors has become the research focus of scholars at home and abroad [65][66][67][68][69][70][71] . Li et al [72] prepared a flexible sensor with the wide monitoring range and ultralow detection limit by ultrasonically anchoring CNTs to TPU electrospun membrane.…”
Section: Introductionmentioning
confidence: 99%
“…[60][61][62][63][64] Selecting suitable materials to prepare various sensors has become the research focus of scholars at home and abroad. [65][66][67][68][69][70][71] Li et al [72] prepared a flexible sensor with a wide monitoring range and ultralow detection limit by ultrasonically anchoring CNTs to TPU electrospun membrane. However, it also shows the disadvantage of a low sensitivity limit, which is less desirable in a condition requiring high sensitivity.…”
Section: Introductionmentioning
confidence: 99%